Teacher Professional Development and Its Influence on Classroom Practices: A Comparative Study Across Different Educational Systems - Ahmad Mulalic (Yayasan Azhar Amanaa Yogyakarta, 2024)
This study investigates the influence of teacher professional development (PD) on classroom practices across various educational systems. By analyzing data from recent literature published within the last seven years, the research aims to identify the most effective components of PD that lead to significant improvements in teaching practices and student outcomes. The study compares the implementation and impact of PD programs across different educational contexts, highlighting the role of instructional coaching, content-focused training, and collaborative learning communities. Findings suggest that PD programs tailored to specific instructional needs, supported by ongoing coaching and collaborative structures, are more likely to yield positive changes in classroom practices. Additionally, the study emphasizes the importance of sustained and contextually relevant PD, which not only enhances teachers' instructional skills but also contributes to their professional growth and retention. The research concludes with recommendations for designing PD initiatives that are both effective and adaptable to the unique demands of diverse educational settings